Policy harmonized approach for the EU agricultural sector modelling - Salputra, Guna; Chantreuil, Frédéric; Hanrahan, Kevin; Donnellan, Trevor; van Leeuwen, Myrna; Erjavec, Emil (MTT Agrifood Research Finland, 2011)
Policy harmonized (PH) approach allows for the quantitative assessment of the impact of various elements of EU CAP direct support schemes, where the production effects of direct payments are accounted through reaction prices formed by producer price and policy price add-ons. Using the AGMEMOD model the impacts of two possible EU agricultural policy scenarios upon beef production have been analysed full decoupling with a switch from historical to regional Single Payment scheme or alternatively with re-distribution of country direct payment envelopes via introduction of EU-wide flat area payment. The PH approach, by systematizing and harmonizing the management and use of policy data, ensures that projected differential policy impacts arising from changes in common EU policies reflect the likely actual differential impact as opposed to differences in how common policies are implemented within analytical models. In the second section of the paper the AGMEMOD model s structure is explained. The policy harmonized evaluation method is presented in the third section. Results from an application of the PH approach are presented and discussed in the paper s penultimate section, while section 5 concludes.
Keywords: Ma; yhdenmukaistaminen; maatalouspolitiikka; maatalousala; mallintaminen; EU-tuet; CAP; agricultural policies; modeling; direct support; decoupling; policy evaluation